Donor–acceptor covalent organic framework promotes visible light-induced oxidative coupling of amines to imines in air. Issue 22 (17th October 2022) - Feng, Jingwen; Cheng, Jie; Pang, Jun; Tang, Mingqiang; Liu, Zewei; Rong, Chunying; Tan, Rong
Abstract : The donor–acceptor COF greatly improved light harvesting and charge separation through a push–pull electron effect, realizing the efficient oxidative coupling of amines to imines with air under visible light irradiation. Abstract : Covalent organic frameworks (COFs) are promising photocatalysts for solar energy utilization due to their tunable band gap for light harvesting. Nevertheless, their photocatalytic performance is often impeded by insufficient charge transfer and rapid charge recombination. Herein, we overcame the bottlenecks by arrangement of complementary donor–acceptor pairs within the COF skeleton to improve the transportation and separation efficiency of photogenerated carriers through a push–pull electron effect. The donor–acceptor COF was synthesized by the polycondensation of electron-donating 1, 3, 5-triformylphloroglucinol (Tp) and electron-accepting 1, 3, 5-triazine-2, 4, 6-triamine (Tt) monomers. Characterization and DFT calculation confirmed greatly improved light harvesting and charge separation due to internal donor–acceptor pairs. As a result, the obtained TpTt-COF is robust and universal in visible light-driven oxidative coupling of amines with air, giving almost quantitative yields (>95%) of various imines within 60 min, while the non-donor–acceptor counterpart was far less efficient. Moreover, the photocatalyst was highly stable and could be facilely recovered from the catalytic system for efficient reuse. The excellent catalytic performance, together with mild reaction conditions (visible light, room temperature, and ambient air), makes TpTt-COF a highly promising photocatalyst for solar application.